MuvB: A Key to Cell Cycle Control in Ovarian Cancer - Audra N. Iness; Larisa Litovchick (Frontiers in Oncology, 2018)
Cancer cells are characterized by uncontrolled proliferation, whereas the ability to enter quiescence or dormancy is important for cancer cell survival and disease recurrence. Therefore, understanding the mechanisms regulating cell cycle progression and exit is essential for improving patient outcomes. The MuvB complex of five proteins (LIN9, LIN37, LIN52, RBBP4, and LIN54), also known as LINC (LIN complex), is important for coordinated cell cycle gene expression. By participating in the formation of three distinct transcriptional regulatory complexes, including DREAM (DP, RB-like, E2F, and MuvB), MMB (Myb-MuvB), and FoxM1–MuvB, MuvB represents a unique regulator mediating either transcriptional activation (during S–G2 phases) or repression (during quiescence). With no known enzymatic activities in any of the MuvB-associated complexes, studies have focused on the therapeutic potential of protein kinases responsible for initiating DREAM assembly or downstream enzymatic targets of MMB. Furthermore, the mechanisms governing the formation and activity of each complex (DREAM, MMB, or FoxM1–MuvB) may have important consequences for therapeutic response. The MMB complex is associated with prognostic markers of aggressiveness in several cancers, whereas the DREAM complex is tied to disease recurrence through its role in maintaining quiescence. Here, we review recent developments in our understanding of MuvB function in the context of cancer. We specifically highlight the rationale for additional investigation of MuvB in high-grade serous ovarian cancer and the need for further translational research.